JINĀS DALAM KITAB FATHUL MU’IN KARYA AHMAD ZAINUDDIN ALFANNANI BAB (SHALAT, ZAKAT, PUASA, HAJI DAN UMRAH, JUAL BELI, DAN IJARAH) (KAJIAN ILMU BADĪ) - Qodariyah, Putri Fatimah; Halim, Muhamad Abdul; Nurlinah, Nurlinah (Hijai - Journal on Arabic Language and Literature, 2019)
This research departs from the fact that the previous books contained many beauties, both in terms of lafadz and meaning. The Fathul Mu'in Book is one of the books written by Ahmad Zainuddin Alfannani, this book discusses the jurisprudence in this book is quite complete covering the chapter thaharah for jinayat or law. The book Fathul Mu'in is one of the books which is more the beauty of language in it, namely jin. Jinn language is the likeness of two lafadz in pronunciation, but the meaning is different. In this study discuss the analysis contained in the Book of Fathul Mu'in, and based on this background, the research is formulated as follows: 1) What is included in the Book of Fathul Mu'in by Ahmad Zainuddin Alfannani Chapter (Prayer, Zakat, Fasting) , Hajj and Umrah, buying and selling, and ijarah) The work of Ahmad Zainuddin Alfannani, 2) Any form of Jinapa which is included in the Book of Fathul Mu'in by Ahmad Zainuddin Alfannani Chapter (Prayer, Zakat, Fasting, Hajj and Umrah, buying and selling, and ijarah) The work of Ahmad Zainuddin Alfannani. This study uses descriptive analysis method, descriptive analysis method is done by describing the facts then followed by analysis. The descriptive method of analysis is not only eye-breaking, but also provides sufficient understanding and explanation of jinÄs in the Fathul Mu'in book by understanding BalÄghah. Â Â Â Â Â Â Â Â Â Â Â After conducting the research, the researcher draws the results of the analysis, that the types and forms of JinÄs contained in the Fathul Mu'in Chapter (Prayer, Zakat, Hajj and Umrah, buying and selling, ijarah) by Ahmad Zainuddin Bin Abdul Aziz Alfannani are: types JinÄs, numbering 87 kinds of JinÄs, which includes 7 types of JinÄs, namely JinÄs tÄm mumÄsil, JinÄs tÄm mustaufi, JinÄs ghair tÄm naqis mudhÅri ', JinÄs tÄm, JinÄs ghair tÄm naqis lÄhi), JinÄs ghair tÄm qolab kul, and JinÄs ghair tÄm qolab ba'di kulk, and Form JinÄs, totaling 145 forms, which consist of fi'il (verb) and isim (noun) arrangement. The fiil is fi'il MÄdi and Fi'il MudÅri. The isim in the book is masdar isim, isim fa'il isim maf'ul and isim jamid.